On Integral Inequalities Involving Generalized Lipschitzian Functions. (6th November 2020) - Jleli, Mohaemd; Samet, Bessem
Abstract : A new class of mappings that includes the class of Lipschitzian mappings is introduced. For this kind of mappings, new integral inequalities of Hadamard's type are obtained. Our results are extensions of many previous contributions related to integral inequalities for Lipschitzian mappings.